2020
DOI: 10.1108/jaar-05-2019-0080
|View full text |Cite
|
Sign up to set email alerts
|

International tax planning techniques: a review of the literature

Abstract: PurposeThis paper aims to understand the international practices of tax planning. International companies choose their capital structure according to differences in international taxation, in order to minimize the tax burden of the whole company group. This paper reviews the literature that deals with international tax avoidance techniques by highlighting tax planning measurements in the empirical literature. The methodology used is the narrative approach of literature review, which consists on assembling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 46 publications
0
34
0
5
Order By: Relevance
“…As mentioned before, what has been researched in previous studies on corporate tax behavior can be applied to tax risk research, by underlying it on the theories and practices. Since Hanlon and Heitzman (2010), Wilde and Wilson (2018), Beer et al (2019), Cooper and Nguyen (2020), Ftouhi andGhardallou (2020), andWang et al (2020) have all reviewed that literature in detail, we can keep our discussion concise and draw the following directions for future research, covering both the determinants and consequences of the tax risk.…”
Section: Literature Gaps and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before, what has been researched in previous studies on corporate tax behavior can be applied to tax risk research, by underlying it on the theories and practices. Since Hanlon and Heitzman (2010), Wilde and Wilson (2018), Beer et al (2019), Cooper and Nguyen (2020), Ftouhi andGhardallou (2020), andWang et al (2020) have all reviewed that literature in detail, we can keep our discussion concise and draw the following directions for future research, covering both the determinants and consequences of the tax risk.…”
Section: Literature Gaps and Future Researchmentioning
confidence: 99%
“…Further, the tax risk can stem from economic risk, tax legislation uncertainty, and inaccurate information processing (Neuman et al 2020). When the corporate tax position is uncertain, which can occur because there is a mismatch between the tax burden and the tax paid to the tax authority, it is associated with the tax risk (Ftouhi and Ghardallou 2020). In this regard, it can be considered that the tax risk is an important construct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It represents an opportunity for tax planning. However, the tax planning effectiveness based on the loopholes is ensured only as long as it is not detected by the tax office (Ftouhi & Ghardallou, 2020).…”
Section: Tax and Tax Planningmentioning
confidence: 99%
“…On the other hand, Ftouhi (2020), Shie, Ou and Wang ( 2014) concluded that higher tax rate will erode tax savings. The erosion is over-emphasized due to varying investment motives of MNEs in the country of operation, tax savings in form of transfer pricing and tax haven will discourage investment decision making (Ftouhi, 2020).…”
Section: Tax Planning and Capital Budgeting Decisionmentioning
confidence: 99%